Blended learning model via small private online course improves active learning and academic performance of embryology. Issue 2 (17th December 2021) - Guo, Yuji; Liu, Haihua; Hao, Aijun; Liu, Shangming; Zhang, Xiaoli; Liu, Huiqing
Abstract: While blended learning has been growing in popularity in recent years, the effectiveness of this procedure remains controversial. In this report, we assess the effectiveness of blended learning of embryology within international medical students. The participants were international medical students taking embryology in the Bachelor of Medicine and Bachelor of Surgery program. The blended learning group (BLG) consisted of students ( n = 43) in the 2018–2019 academic year, taught with blended learning model via a customized small private online course (SPOC). The control traditional teaching group (TTG) consisted students ( n = 48) in the 2017–2018 academic year, taught with traditional teaching model. Academic performance, including mean scores and passing ratios on the final exam of two groups were compared and analyzed with a t ‐test. In addition, a questionnaire directed toward evaluating student's perceptions with the blended learning was administered to students in BLG. The majority of students in BLG actively participated in online self‐study activities and discussion in face‐to‐face class sessions. The mean score and passing ratio were significantly greater than those of students in TTG ( p < 0.01). Results from the questionnaire revealed that the majority of BLG students felt that this method was beneficial for their learning of human embryology. The blended learning model, that integrates SPOC with face‐to‐face class lectures proved a more effective means for the teaching of embryology than the traditional lecture‐based teaching model. This blended learning method may serve as a feasible model that can be readily applied for use in other medical courses.